Ratio of water/fuel concentration in a group of composite droplets on high-temperature heating; Applied Thermal Engineering; Vol. 206 - Antonov D. V. Dmitry Vladimirovich; Kuznetsov G. V. Geny Vladimirovich; Fedorenko R. M. Roman Mikhaylovich; Strizhak P. A. Pavel Alexandrovich (2022, 2022)
Title screen